Idiopathic CD4 lymphocytopenia: An uncommon but fatal cause of Pneumocystis pneumonia - Julia Schearer; Christopher Merrick (Respiratory Medicine Case Reports)
Pneumocystis pneumonia (PCP) is a fungal infection with primary occurrence in immunocompromised individuals by the etiologic agent Pneumocystis jirovecii. In those without previously identified risk factors, maintaining an index of suspicion for this diagnosis with search for underlying immunosuppressive cause is of utmost importance. Here, we present a case of fatal PCP in a patient without a known history of immunocompromise subsequently diagnosed with idiopathic CD4 lymphocytopenia (ICL) with an absolute CD4+ T-cell count of 7 cells/uL.